Dari Lahan Pertanian Ke Landasan Udara: Perubahan Fungsi Lahan Dan Lingkungan Hidup Di Andir Dalam Kebijakan Kolonial (1904–1942) - Muhammad Akmal Siddiq; Sofianto, Kunto; Mahzuni, Dade (PURBAWIDYA, 2025)
This article will discuss the process of land use change in Andir, the factors that led to the construction of the airstrip, and its impact on the surrounding environment and infrastructure. In 1904, the Andir area in Bandung was dominated by rice fields. It was in 1920 that it was decided to build the Andir Airfield, which was built for air defense purposes. The construction of the Andir Airfield had an impact on land use change in Andir. This research uses the historical method, including heuristics, source criticism, interpretation, and historiography, utilizing maps, official documents, and colonial records as the main sources. The results show that the construction of Andir Airfield changed the land function from agricultural areas to aviation infrastructure, which triggered the development of new infrastructure in the area and had a significant impact on the environment.